"Pre-topsurgery, the body scanning machine would most likely error:" Transgender and gender nonconforming travel and tourism experiences. (February 2019) - Olson, Eric D.; Reddy-Best, Kelly
Abstract: Utilizing a qualitative, grounded theory approach, we examined the travel experiences of transgender and gender non-confirming tourists, an under-researched segment of the tourist population. We report findings based on 15 in-depth, semi-structured interviews, which were analyzed for emergent themes. We found that traveling as a transgender and gender non-confirming individual can be complex with at least some or many additional considerations, behavioral changes, and emotional labor related to their gender identity and gender expression when moving into different spaces or situations. Transgender and gender non-confirming tourists often have feelings of fear and anxiety related to sharing and avoiding sharing their gender identity when going through tourist processes related to identification documents, security thresholds, and check-in procedures. However, participants also reported having positive experiences while traveling. Based on these findings, a substantive theory of transgender and gender non-confirming tourist experiences was developed. Highlights: Paper analyzes experiences of 15 transgender and gender non-confirming tourists. In-depth interviews with transgender and gender non-confirming tourists. Traveling as a transgender and gender non-confirming tourist has additional considerations and heighted emotional labor. Feelings of fear and anxiety are often experienced by transgender and gender non-confirming tourists. A theory of transgender and gender non-confirming tourists is developed.